Slap Shot Science : A Curious Fan's Guide to Hockey - Hache, Alain, 1970- (Book collections on Project MUSE., 2015)
"Slap shot science is an under-the-hood, behind-the-scenes, action-packed romp through special moments in the game as seen from the perspective of science and explained in a way everyone can understand"--Back cover.